PENGARUH MODIFIKASI PERMAINAN TERHADAP HASIL BELAJAR PASSING ATAS BOLA VOLI - Robiansyah, Muhammad; Supriatna, Eka; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study refers to the implementation of learning to pass volleyball schedule for two meetings in one semester is still not enough to increase volleyball passing on students. The purpose of this study is to determine the effect of game modification on the results of learning to pass ball volleyball. The methods used in this study is an experimental research form Pre-experimental Design, One-group Pretest-Posttest Design. The subjects in this study were 32 students of Class VIII B of SMP Negeri 4 Sungai Raya. Data analysis with t-test. From the results of statistical calculations it can be concluded that there is a significant effect of game modification on the learning outcomes of passing over volleyball as evidenced from the value of the t-count 9.50 > t-table 1,965 with a significant level of 0.05. While the effect is 18.5%. Keywords: Game Modification, Learning Outcomes, Top Passing.